Automatic Generation of Figural Analogies With the IMak Package - Blum, Diego; Holling, Heinz (Frontiers in Psychology, 2018)
Automatic Item Generation (AIG) techniques are offering innovative ways to produce test items as they overcome many disadvantages involving standard item writing, such as time-consuming work and resource-intensive demands. Although this field is relatively new, it is progressing at a high speed, and several contributions have been accomplished. Nevertheless, a scarce amount of AIG software evidencing favorable psychometric properties of the generated items has been made accessible to the broad scientific community. This research had two goals: first, to present an empirical study of items produced with the aid of the Item Maker (IMak) package available online and, second, to present IMak itself for the automatic generation of figural analogies. We were particularly interested in assessing whether automatically created figural analogy rules could predict item psychometric difficulty. A total of 23 items were generated and administered to 307 participants, 49.51% from Germany. The mean age was 28.61 (SD = 10.19) and 57.65% of the participants were female. Results reveal adequate psychometric properties including convergent validity, that most of the manipulated rules contribute to item difficulty, and that rule-based difficulty prediction is possible to some extent. In other words, psychometric quality of the generated items is supported, which reveals the utility of the IMak package in assessment settings. Finally, the package is presented and its functions for figural analogy item generation are further described.